Sufficiency Criteria for q-Starlike Functions Associated with Cardioid. (19th April 2021) - Zainab, Saira; Shakeel, Ayesha; Imran, Muhammad; Muhammad, Nazeer; Naz, Hira; Malik, Sarfraz Nawaz; Arif, Muhammad
Abstract : This article deals with the q -differential subordinations for starlike functions associated with the lemniscate of Bernoulli and cardioid domain. The primary goal of this work is to find the conditions on γ for 1 + γ z ∂ q   h z / h n   z   ≺ 1 + z, where h z is analytic function and is subordinated by the function which is producing cardioid domain as its image domain while mapping the open unit disk. Along with this, certain sufficient conditions for q -starlikeness of analytic functions are determined.